Gold-loaded carbon nitride nanoparticles for two-photon therapy as well as preparation method and application of gold-loaded carbon nitride nanoparticles

By using gold-loaded carbon nitride nanoparticles (Au/g-C3N4 QDs NPs) in two-photon photodynamic therapy, the problems of short excitation band of photosensitizers and low tissue penetration depth in the prior art are solved, efficient near-infrared light excitation and excellent fluorescence imaging capabilities are achieved, and treatment efficiency is significantly improved.

CN119633112APending Publication Date: 2025-03-18SHENZHEN RES INST OF SHANGHAI JIAOTONG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411827099.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

In existing two-photon photodynamic therapy, the excitation band of photosensitizer is short, the tissue penetration depth is low, and the near-infrared photon energy is low, resulting in low treatment efficiency.

Method used

Gold-supported carbon nitride nanoparticles (Au/g-C3N4 QDs NPs) were used to obtain carbon nitride powder by calcining melamine, and g-C3N4 QDs were obtained by quenching, sonication and centrifugation. Then ascorbic acid and chloroalic acid trihydrate were mixed to reduce the gold, and electrostatically adhered to the surface of g-C3N4 QDs to form Au/g-C3N4 QDs NPs.

Benefits of technology

The near-infrared photoexcitation efficiency is improved, the tissue penetration ability and imaging signal-to-noise ratio are enhanced, and the efficiency and fluorescence imaging ability of two-photon photodynamic therapy are significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119633112A_ABST
    Figure CN119633112A_ABST
Patent Text Reader

Abstract

The invention discloses gold-loaded carbon nitride nanoparticles for two-photon therapy and a preparation method and application thereof.The preparation method comprises the steps that firstly, melamine is ground and then calcined, and carbon nitride powder is obtained; then sequentially carrying out quenching, ultrasonic treatment and centrifugation to prepare a g-C3N4QDs solution; ascorbic acid and chloroauric acid trihydrate are mixed till the color becomes colorless, then the mixture is added to the g-C3N4QDs solution drop by drop, Au0 reduced through ascorbic acid is attached to the surface of g-C3N4QDs through static electricity, and after centrifugation, sediment is taken out, and Au / g-C3N4QDs NPs is obtained. The Au / g-C3N4QDs NPs prepared by the preparation method disclosed by the invention has high near-infrared light excitation efficiency, and the tissue penetrating power and the imaging signal-to-noise ratio are improved; under the excitation of 800nm light, the compound shows excellent fluorescence imaging capability, reactive oxygen generation capability, solubility and biocompatibility, and can be used as a photosensitizer for two-photon photodynamic therapy and two-photon imaging.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of nano materials and their applications, and relates to gold-loaded carbon nitride nanoparticles for two-photon therapy, and a preparation method and application thereof. Background Art

[0002] As a new cancer treatment method, phototherapy has attracted more and more attention. It has also been widely used in clinical practice due to its advantages such as high selectivity, non-invasive or minimally invasiveness, and few side effects. Phototherapy strategies are divided into photodynamic therapy (PDT) and photothermal therapy (PTT). They use light to activate photosensitizers (PS) to produce reactive oxygen species (ROS) or local hyperthermia, thereby changing the intracellular homeostasis and inducing cell apoptosis to achieve the effect of killing tumors. At present, FDA-approved photosensitizers still have the problem of short excitation bands and low tissue penetration depth. They are only suitable for superficial tumor lesions, which greatly limits the scope of application of photodynamic therapy.

[0003] In recent years, near-infrared (NIR) light therapy has developed rapidly, with a high tissue penetration depth, and common excitation wavelengths are generally located in the first near-infrared window (700-900nm). In addition, based on the optical properties of biological tissues, most biological molecules absorb and scatter near-infrared light less than visible light, which greatly improves the efficiency of near-infrared light therapy. However, the energy of near-infrared photons is low, which is often not enough to effectively excite photosensitizers to achieve electronic transitions, thereby reducing the efficiency of photodynamic therapy.

[0004] With the application of near-infrared femtosecond lasers in multiple fields, two-photon photodynamic therapy (TPE-PDT) has gradually developed. TPE-PDT uses NIR femtosecond lasers to excite PS, which not only improves the penetration depth of light therapy, but also provides precise three-dimensional scanning capabilities that are superior to single-photon PDT. Unlike single-photon PS, the two-photon photosensitizer (TPE-PS) required for TPE-PDT needs to have a large two-photon absorption cross-section to ensure efficient ROS yield. In addition, TPE-PS also needs to have two-photon excited fluorescence imaging capabilities to provide imaging and monitoring information for the cancer treatment process.

[0005] Most organic two-photon photosensitizers have poor solubility and biocompatibility in the application of TPE-PDT, which reduces their cancer treatment effect. In recent years, inorganic photosensitizers such as carbon-based nanomaterials, silicon-based nanomaterials, metal nanoparticles and polymers have been reported for use in TPE-PDT. Carbon nanomaterials have attracted much attention due to their advantages such as simple synthesis, low toxicity and low cost. Among them, graphite phase carbon nitride quantum dots (g-C3N4 QDs) are a new type of two-photon photodynamic therapy agent and fluorescence imaging agent. Although g-C3N4 QDs have excellent photochemical stability, biocompatibility and high photocatalytic activity, their excitation bands are mostly in the ultraviolet and visible regions. Therefore, the combination of near-infrared femtosecond lasers and g-C3N4 QDs can realize the application of g-C3N4 QDs in TPE-PDT and two-photon imaging (TPI). However, the near-infrared two-photon (NIR-TPE) photocatalytic activity of g-C3N4 QDs still needs to be further improved. Summary of the invention

[0006] In view of the deficiencies in the prior art, the present invention discloses a gold-loaded carbon nitride nanoparticle for two-photon therapy and a preparation method and application thereof, thereby solving or at least alleviating one or more of the above-mentioned problems and other problems in the prior art.

[0007] The present invention discloses a method for preparing gold-loaded carbon nitride nanoparticles for two-photon therapy, comprising the following steps:

[0008] S1, grinding melamine and calcining it at 400-600° C. for 1-4 hours to obtain carbon nitride powder;

[0009] S2. After calcination is completed, the carbon nitride powder is directly taken out from the muffle furnace and transferred to a container filled with deionized water for quenching;

[0010] S3, subjecting the quenched carbon nitride powder to ultrasonic treatment for 5-60 min;

[0011] S4, after ultrasonic treatment, centrifuge at 3000-8000 rpm for 5-15 min, take the supernatant to obtain a g-C3N4 QDs solution;

[0012] S5, mixing ascorbic acid and chloroauric acid trihydrate in a beaker until the mixture becomes a colorless liquid; wherein the concentration ratio of ascorbic acid to chloroauric acid trihydrate is (35-45):1;

[0013] S6, adding the colorless mixed solution dropwise to the g-C3N4 QDs solution and stirring for 1-3 hours; wherein the ratio of the added volume of the colorless mixed solution to the volume of the g-C3N4 QDs solution is 1:10;

[0014] S7. The stirred solution is centrifuged at 8000-14000 rpm for 5-15 min, and the precipitate below is taken to obtain Au / g-C3N4 QDs nanoparticles.

[0015] Preferably, in step S1, the calcination temperature is 520° C. and the calcination time is 2 h.

[0016] Preferably, in step S2, the mass ratio of carbon nitride powder to ionized water is 1:10; 2.4-2.7 g of carbon nitride can be obtained after calcining 3.0 g of melamine, and the corresponding volume of deionized water is 24-27 mL.

[0017] Preferably, in step S4, the ultrasonic treatment is followed by centrifugation at 5000 rpm for 10 min.

[0018] Preferably, in step S5, the concentration ratio of ascorbic acid to chloroauric acid trihydrate is 40:1.

[0019] Preferably, in step S5, the concentration of chloroauric acid trihydrate is 1 mM, and the concentration of ascorbic acid is 0.35 mg / mL.

[0020] Preferably, in step S7, the size of the obtained Au / g-C3N4 QDs nanoparticles is 50-90 nm.

[0021] Furthermore, the present invention provides gold-loaded carbon nitride nanoparticles for two-photon therapy prepared by the preparation method described above.

[0022] In addition, the present invention also provides the use of gold-loaded carbon nitride nanoparticles for two-photon therapy prepared by the preparation method described above in the preparation of two-photon photodynamic therapy preparations.

[0023] Preferably, in the application, the effective concentration of gold-loaded carbon nitride nanoparticles used for two-photon therapy is 200 μg / ml.

[0024] The present invention has the following beneficial effects:

[0025] This technical solution obtains carbon nitride powder by calcining melamine, and then uses deionized water to quench, ultrasonicate and centrifuge in sequence to obtain a g-C3N4 QDs solution, then mixes ascorbic acid and trihydrate chloroauric acid until the color becomes colorless and then adds them dropwise to the g-C3N4 QDs solution. Au0 reduced by ascorbic acid is electrostatically attached to the surface of g-C3N4 QDs, and then the surface precipitate is removed after centrifugation to obtain Au / g-C3N4 QDs NPs, which have high near-infrared light excitation efficiency, and improved tissue penetration ability and imaging signal-to-noise ratio; under 800nm ​​light excitation, it exhibits excellent fluorescence imaging ability, reactive oxygen generation ability, excellent solubility and biocompatibility, and can be used as a photosensitizer for two-photon photodynamic therapy and two-photon imaging. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the specific embodiments of the present disclosure, the following briefly introduces the drawings required for use in the specific embodiments. In all the drawings, each element or part is not necessarily drawn according to the actual scale.

[0027] Figure 1 TEM image of Au / g-C3N4 QDs NPs of the embodiment of the present invention;

[0028] Figure 2 The XRD and UV absorption spectra of Au / g-C3N4 QDs NPs in the embodiment of the present invention;

[0029] Figure 3 The single-photon and two-photon emission spectra of Au / g-C3N4 QDs NPs in the embodiment of the present invention;

[0030] Figure 4 This is a graph showing the oxygen activity detection curve of Au / g-C3N4 QDs NPs in an embodiment of the present invention.

[0031] Figure 5 These are confocal images of ROS generated by Au / g-C3N4 QDs NPs in living cells after two-photon exposure for different time periods according to an embodiment of the present invention. DETAILED DESCRIPTION

[0032] The following embodiments of the technical solution of the present disclosure are described in detail in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present disclosure, and are therefore only used as examples, and cannot be used to limit the protection scope of the present disclosure.

[0033] It should be noted that, unless otherwise specified, the technical terms or scientific terms used in this application should have the common meanings understood by those skilled in the art to which the present invention belongs.

[0034] Example 1

[0035] Samples: melamine (analytical grade, Maclean), ascorbic acid (analytical grade, Aladdin), chloroauric acid trihydrate (analytical grade, Aladdin).

[0036] Preparation method of Au / g-C3N4 QDs nanoparticles (Au / g-C3N4 QDs NPs)

[0037] After testing with a variety of methods, the final experimental data confirmed that gold-loaded carbon nitride was synthesized using melamine, ascorbic acid and trihydrated chloroauric acid as raw materials. The specific preparation method is as follows:

[0038] S1. Weigh 3.0 g of melamine and grind it in an agate mortar for 30 min. Then take it out and put it in a crucible. Then put the crucible into a muffle furnace for calcination at a temperature of 400-600° C. for 1-4 h to obtain carbon nitride powder (C3N4);

[0039] S2. After calcination is completed, the crucible is directly taken out from the muffle furnace, and the carbon nitride powder obtained after calcination in the crucible is transferred to a beaker filled with deionized water for quenching;

[0040] S3, placing the beaker after completing step S2 into an ultrasonic crusher for ultrasonic treatment, the ultrasonic treatment time is 5-60 minutes; the purpose of the ultrasonic crusher for ultrasonic treatment is to uniformly disperse the carbon nitride powder in deionized water and form g-C3N4 QDs;

[0041] S4, taking the beaker out of the ultrasonic crusher, and placing the beaker in a centrifuge and centrifuging at 3000-8000 rpm for 5-15 min, taking the supernatant and storing it in the beaker to obtain a g-C3N4 QDs solution;

[0042] S5, mixing ascorbic acid (AA) and chloroauric acid trihydrate (HAuCl4·3H2O) in a beaker until the mixture becomes a colorless liquid; wherein the concentration ratio of AA to HAuCl4·3H2O is (35-45):1;

[0043] S6, adding the colorless mixed solution dropwise to the g-C3N4 QDs solution, the ratio of the added volume of the colorless mixed solution to the volume of the g-C3N4QDs solution is 1:10, and stirring for 1-3h; reducing trihydrate chloroauric acid to 0-valent gold particles (Au0) under the action of ascorbic acid, and the 0-valent gold particles are electrostatically adsorbed on the surface of g-C3N4QDs to form gold-loaded carbon nitride quantum dots (Au / g-C3N4QDs);

[0044] S7. Centrifuge the solution containing Au / g-C3N4 QDs in S6 at 8000-14000 rpm for 5-15 min, and take the precipitate below to obtain Au / g-C3N4 QDs nanoparticles (Au / g-C3N4 QDs NPs).

[0045] The beakers referred to in steps S2, S4 and S5 are different beakers. The mass ratio of carbon nitride powder to ionized water is 1:10; 2.4-2.7 g of carbon nitride can be obtained after calcining 3.0 g of melamine, and the corresponding volume of deionized water is 24-27 mL.

[0046] In different tests, the ground melamine can be calcined in a muffle furnace at 400-600°C for 1-4h; preferably, the calcination temperature is 520°C and the calcination time is 2h. After the carbon nitride powder is quenched, it can be ultrasonically treated for 5-60min, preferably for 10min, in order to allow the quenched C3N4 to be better dispersed in deionized water and form g-C3N4 QDs. The ultrasonically treated solution is then centrifuged in a centrifuge at 3000-8000rpm for 5-15min, preferably at 5000rpm for 10min. In step S5, the concentration ratio of AA and HAuCl4·3H2O can be (35-45):1; preferably, the concentration ratio of AA and HAuCl4·3H2O is 40:1. In step S6, stirring can be performed for 1-3 hours, preferably for 2 hours, in order to allow the reduced Au0 to be electrostatically adsorbed on the surface of g-C3N4 QDs to form Au / g-C3N4 QDs. In step S7, centrifuge at 8000-14000 rpm for 5-15 minutes, preferably at 12000 rpm for 10 minutes.

[0047] In one embodiment, the concentration ratio of AA to HAuCl4·3H2O is preferably 40:1, HAuCl4·3H2O (1mL, 1mM) and AA (50μL, 0.35mg / mL) are mixed for 1min until the color changes to a colorless mixture; 1mL of the colorless mixture is then added dropwise to 10mL of g-C3N4 QDs (0.1mg / mL) solution and stirred for 2h. This embodiment can effectively control the growth or growth of the reduced Au0, so that Au0 can be better attached to the surface of g-C3N4 QDs in a discrete distribution.

[0048] It is worth noting that in step S5-S6, AA is used as a reducing agent with moderate reducing property, which can ensure that Au0 reduced from HAuCl4·3H2O can be well loaded on the two-dimensional lamellar surface of g-C3N4 QDs, that is, multiple Au0 particles can be electrostatically adsorbed on the surface of the same g-C3N4 QDs in a discrete distribution to form gold-loaded carbon nitride quantum dots (Au / g-C3N4 QDs), and the growth of Au0 is effectively avoided. If a reducing agent with weak reducing property is selected, the reduction reaction will not occur for a long time in step S5-S6; if a reducing agent with strong reducing property is selected, the Au in HAuCl4·3H2O in step S5-S6 will be quickly reduced, and the smaller Au0 will grow into larger particles through aggregation and fusion to form precipitation, which will reduce the attachment points of the reduced Au0 on the surface of g-C3N4 QDs, thereby affecting the performance of Au / g-C3N4 QDs.

[0049] Test of Au / g-C3N4 QDs Nanoparticles (Au / g-C3N4 QDs NPs)

[0050] 1. Characterization of the morphology and lattice structure of Au / g-C3N4 QDs NPs

[0051] like Figure 1 As shown in (a) and 1(b), the size of g-C3N4 QDs nanoparticles is about 30-70nm, and the average size of Au / g-C3N4 QDs nanoparticles after loading Au increases to 50-90nm. Figure 1 c shows the high-resolution TEM (transmission electron microscopy) of Au / g-C3N4 QDs nanoparticles, whose lattice spacing is about 0.14 nm, indicating that Au / g-C3N4 QDs NPs were successfully synthesized.

[0052] 2. XRD and UV absorption spectrum test of Au / g-C3N4 QDs NPs

[0053] Figure 2 (a) is the XRD spectra of g-C3N4 QDs and Au / g-C3N4 QDs. The diffraction peaks of g-C3N4 QDs are located at 13.0° and 27.3°, while the diffraction peaks of Au nanoclusters are located at 38.4°, 44.6° and 65.0°, and the corresponding crystal planes are (111), (200) and (220), respectively. Figure 2 (b) It can be concluded that the absorption peak of g-C3N4 QDs is mainly located in the ultraviolet region (the wavelength range of ultraviolet light is 10nm-400nm); the absorption of Au / g-C3N4 QDs in the visible-near infrared region is significantly enhanced, that is, the absorption is significantly enhanced in the 800nm ​​region of the wavelength range of near-infrared light.

[0054] 3. Fluorescence spectrum test of Au / g-C3N4 QDs NPs

[0055] Figure 3 (a) Single photon (PL) fluorescence spectra of g-C3N4 QDs and Au / g-C3N4 QDs. Figure 3 (b) Two-photon (TPL) fluorescence spectra of g-C3N4 QDs and Au / g-C3N4 QDs. Figure 3 As shown, the single-photon and two-photon fluorescence spectra of both are in the blue light region (blue light wavelength range 400nm-500nm), and the gold loading does not affect the emission wavelength of carbon nitride, but the fluorescence intensity of Au / g-C3N4 QDs is weakened.

[0056] 4. Test of the viability of Au / g-C3N4 QDs NPs

[0057] The ROS generation capacity of g-C3N4 QDs and Au / g-C3N4QDs was detected by DCFH (2,7-dichlorodihydrofluorescein) probe, and 2,7-dichlorodihydrofluorescein diacetate (DCF-DA) was used as a ROS indicator. Under the illumination of 800nm ​​near-infrared femtosecond laser, the ROS generated by the two carbon nitride quantum dots at different times under 800nm ​​single-photon excitation are shown in Figure 2. Figure 4 As shown. DCF-DA gradually increases over time, indicating that ROS are generated and gradually increase. Under the same illumination time, Au / g-C3N4 QDs have a relatively strong ability to generate ROS and have a high near-infrared light excitation efficiency. This result is consistent with the above-mentioned fluorescence spectrum test. Fluorescence emission and catalytic ability are relative. When the fluorescence emission ability is enhanced, its photocatalytic activity decreases.

[0058] 5. Intracellular ROS test of Au / g-C3N4 QDs NPs

[0059] A certain amount of human breast cancer cells (MCF-7 cells) were cultured in a fresh culture medium containing g-C3N4 QDs (200 μg / ml), and the same amount of MCF-7 cells were cultured in a fresh culture medium containing Au / g-C3N4 QDs (200 μg / ml). After the culture was completed, the intensity changes of green fluorescence at different times under 800nm ​​near-infrared femtosecond laser irradiation were photographed using a two-photon confocal microscope. Figure 5 Confocal images of ROS generated by g-C3N4 QDs NPs and Au / g-C3N4 QDs NPs in living cells after two-photon exposure for different times. Figure 5This is a confocal image of living cells cultured in culture medium containing g-C3N4 QDs NPs and Au / g-C3N4 QDsNPs after two-photon scanning. It can be seen from the figure that after 5 minutes of scanning, there is obvious fluorescence emission compared with the blank group, which further proves the generation of ROS in living cells for TPE-PDT and TPI; and the green fluorescence intensity of Au / g-C3N4 QDs NPs in living cells is significantly stronger than that of g-C3N4 QDs NPs in living cells, which effectively improves the tissue penetration ability and imaging signal-to-noise ratio, and also shows that Au / g-C3N4 QDsNPs have good solubility and biocompatibility.

[0060] The above embodiments are only used to illustrate the technical solutions of the present disclosure, rather than to limit them. Although the present disclosure has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. These modifications or replacements do not deviate the essence of the corresponding technical solutions from the scope of the technical solutions of the embodiments of the present disclosure, and they should all be included in the scope of the claims and specification of the present disclosure.

Claims

1. A method for preparing gold-loaded carbon nitride nanoparticles for two-photon therapy, characterized in that: The steps include: S1, grinding melamine and calcining it at 400-600° C. for 1-4 hours to obtain carbon nitride powder; S2. After calcination is completed, the carbon nitride powder is directly taken out from the muffle furnace and transferred to a container filled with deionized water for quenching; S3, subjecting the quenched carbon nitride powder to ultrasonic treatment for 5-60 min; S4, after ultrasonic treatment, centrifuge at 3000-8000 rpm for 5-15 min, take the supernatant to obtain a g-C3N4QDs solution; S5, mixing ascorbic acid and chloroauric acid trihydrate in a beaker until the mixture becomes a colorless liquid; wherein the concentration ratio of ascorbic acid to chloroauric acid trihydrate is (35-45):1; S6, adding the colorless mixed solution dropwise to the g-C3N4 QDs solution and stirring for 1-3 hours; wherein the ratio of the added volume of the colorless mixed solution to the volume of the g-C3N4 QDs solution is 1:10; S7. The stirred solution is centrifuged at 8000-14000 rpm for 5-15 min, and the precipitate below is taken to obtain Au / g-C3N4QDs nanoparticles.

2. The method for preparing gold-loaded carbon nitride nanoparticles for two-photon therapy according to claim 1, characterized in that: In the step S1, the calcination temperature is 520° C. and the calcination time is 2 hours.

3. The method for preparing gold-loaded carbon nitride nanoparticles for two-photon therapy according to claim 1, characterized in that: In the step S2, the mass ratio of carbon nitride powder to ionized water is 1:10; 2.4-2.7 g of carbon nitride can be obtained after calcining 3.0 g of melamine, and the corresponding volume of deionized water is 24-27 mL.

4. The method for preparing gold-loaded carbon nitride nanoparticles for two-photon therapy according to claim 1, characterized in that: In the step S4, the solution is centrifuged at 5000 rpm for 10 min after ultrasonic treatment.

5. The method for preparing gold-loaded carbon nitride nanoparticles for two-photon therapy according to claim 1, characterized in that: In step S5, the concentration ratio of ascorbic acid to chloroauric acid trihydrate is 40:

1.

6. The method for preparing gold-loaded carbon nitride nanoparticles for two-photon therapy according to claim 5, characterized in that: In step S5, the concentration of chloroauric acid trihydrate is 1 mM, and the concentration of ascorbic acid is 0.35 mg / mL.

7. The method for preparing gold-loaded carbon nitride nanoparticles for two-photon therapy according to claim 1, characterized in that: In step S7, the size of the obtained Au / g-C3N4 QDs nanoparticles is 50-90 nm.

8. Gold-loaded carbon nitride nanoparticles for two-photon therapy prepared by the preparation method according to any one of claims 1 to 7.

9. Use of the gold-loaded carbon nitride nanoparticles for two-photon therapy as claimed in claim 8 in the preparation of two-photon photodynamic therapy preparations.

10. The use according to claim 9, characterized in that: The effective concentration of gold-loaded carbon nitride nanoparticles for two-photon therapy is 200 μg / ml.